Long Covid stigma: Estimating burden and validating scale in a UK-based sample - Pantelic, Marija; Ziauddeen, Nida; Boyes, Mark; O’Hara, Margaret E.; Hastie, Claire; Alwan, Nisreen A. (PLOS ONE, 2022)
Background Stigma can be experienced as perceived or actual disqualification from social and institutional acceptance on the basis of one or more physical, behavioural or other attributes deemed to be undesirable. Long Covid is a predominantly multisystem condition that occurs in people with a history of SARSCoV2 infection, often resulting in functional disability. This study aimed to develop and validate a Long Covid Stigma Scale (LCSS); and to quantify the burden of Long Covid stigma. Methods Data from the follow-up of a co-produced community-based Long Covid online survey using convenience non-probability sampling was used. Thirteen questions on stigma were designed to develop the LCSS capturing three domains–enacted (overt experiences of discrimination), internalised (internalising negative associations with Long Covid and accepting them as self-applicable) and anticipated (expectation of bias/poor treatment by others) stigma. Confirmatory factor analysis tested whether LCSS consisted of the three hypothesised domains. Model fit was assessed and prevalence was calculated. Results 966 UK-based participants responded (888 for stigma questions), with mean age 48 years (SD: 10.7) and 85% female. Factor loadings for enacted stigma were 0.70–0.86, internalised 0.75–0.84, anticipated 0.58–0.87, and model fit was good. The prevalence of experiencing stigma at least ‘sometimes’ and ‘often/always’ was 95% and 76% respectively. Anticipated and internalised stigma were more frequently experienced than enacted stigma. Those who reported having a clinical diagnosis of Long Covid had higher stigma prevalence than those without. Conclusion This study establishes a scale to measure Long Covid stigma and highlights common experiences of stigma in people living with Long Covid.